1984
DOI: 10.1111/j.1365-2133.1984.tb15590.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous penetration in the hairless dog, weanling pig and grafted athymic nude mouse: evaluation of models for predicting skin penetration in man

Abstract: The human skin grafted congenitally athymic (nude) mouse, pig skin grafted nude mouse, hairless dog, and weanling Yorkshire pig were evaluated as models for predicting skin penetration in man. Nine radiolabelled compounds previously tested on man were applied topically (4 micrograms/cm2) to each model. These compounds included caffeine, benzoic acid, N, N-diethyl-m-toluamide, three steroids, and three insecticides. To correct for incomplete excretion of the label following topical absorption, per cent penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(43 citation statements)
references
References 9 publications
(5 reference statements)
3
37
1
1
Order By: Relevance
“…Experiments with other chemical compounds resulted in the same conclusion, namely that porcine skin often yielded permeation values similar to those of human skin [42,56]. Comparative studies designed to predict skin permeation in man concluded that similar permeation values were obtained between pig and human skin when tested under identical conditions in vitro [43]. Permeation of paraquat, carbaryl, aldrin and fluazifop-butyl were also very close in man and pig skin [49].…”
supporting
confidence: 54%
“…Experiments with other chemical compounds resulted in the same conclusion, namely that porcine skin often yielded permeation values similar to those of human skin [42,56]. Comparative studies designed to predict skin permeation in man concluded that similar permeation values were obtained between pig and human skin when tested under identical conditions in vitro [43]. Permeation of paraquat, carbaryl, aldrin and fluazifop-butyl were also very close in man and pig skin [49].…”
supporting
confidence: 54%
“…This value is within the range of estimates for transdermal absorption of other organophosphorus insecticides (e.g. malathion, parathion and chlorpyrifos) of 5-60% [5,33,35,41]. Similarly, percutaneous absorption of methyl parathion by human skin in vitro was 1-5% [21].…”
Section: Discussionsupporting
confidence: 62%
“…Likewise, the pattern of inhibition caused by oral administration of methyl parathion is consistent with high, albeit delayed, oral absorption and rapid clearance [7,26]. The slower onset of cholinesterase inhibition following dermal administration of methyl parathion correlates with a low dermal absorption coefficient resulting from limited penetration of the stratum corneum as well as sequestration within a lipophilic compartment in the dermis [9,13,24,31,41]. A slow redistribution from the dermis can also account for both a sustained increase in blood methyl parathion concentration [26] and prolonged inhibition of cholinesterase activity.…”
Section: Discussionmentioning
confidence: 87%